The body mass index change is associated with death or hemodialysis transfer in Japanese patients initiating peritoneal dialysis - Daiki Kojima; Naoki Washida; Kiyotaka Uchiyama; Eriko Yoshida Hama; Tomoki Nagasaka; Ei Kusahana; Takashin Nakayama; Kengo Nagashima; Yasunori Sato; Kohkichi Morimoto; Takeshi Kanda; Hiroshi Itoh (Renal Failure)
A decreased body mass index (BMI) over time is associated with a poor prognosis for patients on hemodialysis. We aimed to examine whether this association also applies to patients with peritoneal dialysis (PD). BMI change was defined as the percentage change in the BMI between the time of PD catheter insertion and six months after its insertion. The association between the BMI change and all-cause mortality or PD discontinuation from six months after PD catheter insertion until October 2021 was investigated. This retrospective cohort study included 122 patients (aged 61.1 ± 12.1 years; 90 males) who underwent PD catheter insertion between January 2008 and March 2020. The median follow-up period was 43.1 (21.2–78.8) months. The median six-month percentage change in the BMI was −2.14 (−5.56–1.84)%, and patients were categorized into tertiles based on their BMI changes. The fully-adjusted Cox regression analysis revealed a significantly higher rate of PD discontinuation or all-cause mortality (hazard ratio (HR): 2.48; 95%; confidence interval (CI): 1.41–4.37) in patients with the lowest tertile (T1, BMI change: < −4.13%) compared to patients with the middle tertile (T2, BMI change: −4.13%–0.67%). The risk was not significantly higher in patients with the highest tertile (T3, BMI change: >0.67%) than those in the T2 group (HR: 1.18; 95% CI: 0.66–2.11). A decreased BMI over time is independently associated with HD transfer or all-cause mortality among patients initiating PD, which highlights the importance of the 6-month BMI change as a novel prognostic marker.